Antibacterial Screening of Mangrove Extract Library Showed Potential Activity against Escherichia coli and Staphylococcus aureus - Audah, Kholis Abdurachim; Batubara, Razethy; Julkipli, Julkipli; Wijaya, Elza; Kurniawaty, Evi; Batubara, Irmanida (Journal of Tropical Life Science, 2020)
Humans are at a continuous battle against different types of diseases, so that extraordinary effort to accelerate drug discovery has become a necessity. Indonesian biodiversity is abundant natural resources that can be utilized as potential drug sources. Mangroves are among potential plant medicines that grow nearly at all Indonesian coastlines. The aim of this study was to evaluate the potential of mangrove extracts (extract library) as antibacterial agents. In this study, eight mangroves species with 16 samples from different parts of the plants such as leaf, bark or root were collected. Four types of solvents with different polarity, namely water, ethanol, ethyl acetate and hexane were used in maceration of samples producing 64 extracts. Disk diffusion method was used for antibacterial screening using five bacterial strains. There were 37 extracts showed antibacterial potential with the lowest and the highest inhibition indexes were 0.0283 and 1.8983, respectively. The highest inhibition index was recorded for ethyl acetate extract of Bruguiera gymnorrhiza root (BgR (Ea)) against Escherichia coli. The second highest inhibition index was 0.7867 recorded water extract of Avicennia marina leaf (AmL (A)) against Staphylococcus aureus. Almost all of extract showed saponin and tannin in considerable amount. This supported the data that mangrove extracts were potential as antibacterial agents.